1999
DOI: 10.1074/jbc.274.45.32112
|View full text |Cite
|
Sign up to set email alerts
|

Unique Cellular Events Occurring during the Initial Interaction of Macrophages with Matrix-retained or Methylated Aggregated Low Density Lipoprotein (LDL)

Abstract: A critical event in atherogenesis is the interaction of arterial wall macrophages with subendothelial lipoproteins. Although most studies have investigated this interaction by incubating cultured macrophages with monomeric lipoproteins dissolved in media, arterial wall macrophages encounter lipoproteins that are mostly bound to subendothelial extracellular matrix, and these lipoproteins are often aggregated or fused. Herein, we utilize a specialized cell-culture system to study the initial interaction of macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 72 publications
(82 reference statements)
4
52
0
Order By: Relevance
“…In the first study, we showed that macrophages plated on top of SMase-aggregated and matrix-retained LDL internalized and degraded this material over a 24-h period and accumulated large amounts of intracellular, ACAT-derived CE (21). In the second study, we focused on the very earliest events that occur when macrophages first engage matrix-retained lipoproteins (22). During this period, there is prolonged cell-surface contact …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the first study, we showed that macrophages plated on top of SMase-aggregated and matrix-retained LDL internalized and degraded this material over a 24-h period and accumulated large amounts of intracellular, ACAT-derived CE (21). In the second study, we focused on the very earliest events that occur when macrophages first engage matrix-retained lipoproteins (22). During this period, there is prolonged cell-surface contact …”
Section: Discussionmentioning
confidence: 99%
“…with relatively little LDL-protein degradation but much more LDL-CE hydrolysis (22). The actual quantity of cholesterol internalized during this period of "selective lipid uptake" is probably not large.…”
Section: Degradation Of Matrix-retained Ldl By Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…LDL was isolated from human plasma by preparative ultracentrifugation at d ϭ 1.063 g/dl (17) and was labeled with 125 I using Iodogen-coated tubes (Pierce) and Na[ 125 I] as described previously (18); the labeled LDL had a specific activity of 150 -300 cpm/ng protein and was used within 3 weeks of iodination. Lipoprotein-depleted serum (LPDS) was prepared from fetal bovine serum by preparative ultracentrifugation at d ϭ 1.21 g/dl.…”
Section: Methodsmentioning
confidence: 99%